Edukasi Upaya Pencegahan Demam Berdarah Dengue di Wilayah Kerja Puskesmas Tanjung Karang - Elisa Oktaviana; Winda Nurmayani (Insan Kreasi Media, 2024)
Dengue hemorrhagic fever (DHF) is one of the most common health problems in society which causes various health problems. This disease is caused by the bite of the Aedes Aegypti mosquito which transmits the dengue virus. In the Tanjung Karang Community Health Center working area, 96 residents in the last 2 years have been affected by dengue fever. The aim of implementing this community service is to provide education to people who have been affected by dengue fever so that they have a higher level of knowledge in efforts to prevent dengue fever. This community service program is implemented using the Asset Based Community Development method. The population in this study were all residents who had experienced dengue fever in the Tanjung Karang Community Health Center working area. The total number of dengue fever cases in the Tanjung Karang Community Health Center working area from 6 sub-districts, namely from January 2021 to August 2022, was 96 people. Then it was entered into the Slovin formula with an error rate of 0.05 and the result was 77.41, so the researchers took 77 people as respondents. Education can increase knowledge about dengue prevention efforts in the community to knowledge that was previously quite good. It is hoped that the community will play an active role in carrying out environmental cleanliness, especially in carrying out the eradication of mosquito nests in order to reduce as little as possible the opportunity for mosquitoes to nest and breed by carrying out draining, closing water reservoirs both outside the house and inside the house and burning used items. Communities who have higher knowledge can be empowered as leaders in efforts to prevent DHF.